HUBUNGAN ANTARA KEMAMPUAN MUHADATSAH DENGAN NILAI TOAFL DI STAIN CURUP - Noza Aflisia (Institut Agama Islam Negeri (IAIN) Metro, 2018)
To measure the level of Arabic skill of students in State Collage For Islamic Studies Curup addition to the value obtained directly from the lecturers Arabic, the skill of Arabic can also be known through the TOAFL. TOAFL results obtained by students vary and have interesting phenomena to be examined by the author. There are among students who have good muhadatsah skills but get a low TOAFL score, some also have less muhadatsah skill, but get high TOAFL score. With this research is expected to find whether there is a relationship between the muhadatsah skill of State Collage For Islamic Studies Curup students with TOAFL score. Then how significant the corelation both of them. The approach of this research is quantitative descriptive, with correlation method. The primary data source is the student's muhadatsah score and the TOAFL score. Data collection techniques used in this study are interviews, documentation and observation. To know the relationship between variables x and y used correlation coefficient analysis using Product Moment formula. The result of this research is there is positive relation with medium category between muhadatsah skill with score of TOAFL student of State Collage For Islamic Studies Curup. It also found other factors that affect the score of TOAFL, namely good psychological conditions, healthy physical, precise strategy, experience and luck